Validation of a High-Performance Liquid Chromatographic Method with Fluorecence Detection for the Quantification of Flurbiprofen in Tablets - Thi Thanh Binh, Nguyen; Anh, Tran Mai; Thuan, Duong Hai; Tung, Nguyen Huu; Tung, Bui Thanh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 2DO - 10.25073/2588-1132/vnumps.4121, 2018)
Abstract:  This study develops a high-performance liquid chromatographic method with fluorecence detection for the quantification of flurbiprofen in tablets. A C 8 reverse phase column (5 μm, 120 Å, 4.6×150 mm) was used with a mobile phase of acetonitrile: water: glacial acetic acid (65 : 32.5 : 2.5, v/v/v). The flow rate was 1 ml/min and the column effluent was monitored within 8 minutes. The excitation wave length and emission wave length were 247 nm and 312 nm, respectively. The temperature of flow cell was set at 45˚C and detector sensitivity was 5. The retention time of flurbiprofen was found to be 3.78 minutes. The method was validated under the concentration range of 5 - 100 ng/ml with a tight linear correlation between peak area and sample concentration (R = 0.9999). The proposed method was found to be specific to flurbiprofen, accurate and precise. The percentage recovery was ≤ 100 ± 2%, the relative standard deviation of the repeatability was ≤ 2.08% and the relative standard deviation of the intermediate precision was ≤ 2.96%. The limit of detection and limit of quantification were 0.010 and 0.025 ng/ml, respectively. Keywords: Flurbiprofen, quantification, high-performance liquid chromatography, fluorecence detection. References: [1] Maroof K, Zafar F, Ali H, Naveed S. Flurbiprofen: A Potent Pain Reliever. J Bioequiv Availab. 2015; 7 (1): 056-058 [2] Thebault JJ, Lagrue G, Blatrix CE, Cheynier L, Cluzan R. Clinical pharmacology of flurbiprofen: a novel inhibitor of platelet aggregation. Curr Med Res Opin. 1977; 5 (1): 130-134 [3] Geerts H. Drug evaluation: (R)-flurbiprofen - an enantiomer of flurbiprofen for the treatment of Alzheimer's disease. Idrugs. 2007; 10 (2): 121-133. [4] McGeer PL, Schulzer M, McGeer EG. Arthritis and anti-inflammatory agents as possible protective factors for Alzheimer's disease A review of 17 epidemiologic studies. Neurology. 1996; 47 (2): 425-432. [5] Meister S, Zlatev I, Stab J, Docter D, Baches S, et al. Nanoparticulate flurbiprofen reduces amyloid-β 42 generation in an in vitro blood-brain barrier model. Alzheimer's research & therapy. 2013; 5 (6): 51-63. [6] Drugbank. http://www.drugbank.ca. Flurbiprofen. Consulted jun 20th 2017. [7] Bhaskar K, Anbu J, Ravichandiran V, Venkateswarlu V, Rao YM. Lipid nanoparticles for transdermal delivery of flurbiprofen: formulation, in vitro, ex vivo and in vivo studies. Lipids in health and disease. 2009; 8: 6-21. [8] Gonzalez-Mira E, Egea MA, Souto EB, Calpena AC, Garcia ML. Optimizing flurbiprofen-loaded NLC by central composite factorial design for ocular delivery. Nanotechnology. 2010; 22 (4): 045101. [9] Zhao X, Li W, Luo Q, Zhang X. Enhanced bioavailability of orally administered flurbiprofen by combined use of hydroxypropyl-cyclodextrin and poly (alkyl-cyanoacrylate) nanoparticles. European journal of drug metabolism and pharmacokinetics. 2014; 39 (1): 61-67. [10] European Pharmacopoeia Commission. European Pharmacopoeia 9th edition. 2017. [11] Bilal Y, Emrah A. Spectrofluorometric and UV Spectrophotometric Methods for the Determination of Flurbiprofen in Pharmaceutical Preparations. Journal of Pharmaceutical Analysis. 2015; 4 (4): 1-8 [12] Nguyễn TTB, Đặng NA, Trần MA, Nguyễn TH. Xây dựng quy trình định lượng flurbiprofen trong viên nén bao phim 100 mg bằng phương pháp sắc ký lỏng hiệu năng cao ghép đầu dò diode-array. Tạp chí Khoa học ĐHQGHN: Khoa học Y Dược. 2017; 33 (2): 41-49 [13] Chenghan M, Bin L, Qiangfeng Y, Jing J, Ting X, et al. Liquid chromatography-tandem mass spectrometry for the quantification of flurbiprofen in human plasma and its application in a study of bioequivalence. Journal of Chromatography B. 2015; 993-994: 69-74. [14] Lee HI, Choi CI, Byeon CY, Lee JE, Park SY, et al. Simultaneous determination of flurbiprofen and its hydroxy metabolite in human plasma by liquid chromatography-tandem mass spectrometry for clinical application. Journal of chromatography B. 2014; 971: 58-63. [15] Mano N, Narui T, Nikaido A, Goto J. Separation and determination of diastereomeric flurbiprofen acyl glucuronides in human urine by LC/ESI-MS with a simple column-switching technique. Drug Metabol Pharmacokin. 2002; 17: 142-149. [16] Yilmaz B, Emrah A. Determination of flurbiprofen in pharmaceutical preparations by GC–MS. Arabian Journal of Chemistry. 2015; 59: 38-44. [17] European Medicines Agency. Guideline on bioanalytical method validation. 2011; 9-10. [18] The International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use. Validation of analytical procedures: text and methodology Q2(R1). 2005; 6-13. [19] United States Pharmacopeial Convention. United States Pharmacopoeia 40–NF 35. 2017.